Cholestatic jaundice in a sample of Iraqi Infants (A hospital based study) - Al-Azzawi, Sawsan I.; Al-Badri, Bayan A.; Mohammad, Lana A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cholestatic Jaundice is a dilemma facing not only the primary care provider but also the specialist pediatricians in our country.Subjects & methods: Analysis of 50 cases of cholestatic jaundice aged 3 weeks- 18 months were carried out over 18 months in the Gastroenterology & Hepatology unit in the Children Welfare Teaching Hospital, Medical City, and Baghdad. Clinical, biochemical, radiological and histopathological results were recorded.Results: Fifty patients with Cholestatic Jaundice, 28 males &22 females, were evaluated. The main causes of Cholestatic Jaundice were Biliary Atresia in 22 cases (44%)(the mean age of presentation was 4.1 months ), and Neonatal Hepatitis Syndrome of different etiology in 17 cases (34%) (The mean age of presentation was 5.9 months).Galactosemia was the most common cause of metabolic liver disease and CMV was the commonest of the intrauterine viral infections. Two cases of choledocal cyst (4%) and no definite cause was found in 9 cases (18%)Conclusion: Biliary atresia was the most common cause of cholestasis in this study of extra-hepatic type. Different stages of cirrhosis were found in almost all cases of biliary Atresia because of delayed presentation. Clay color stool, hepatomegaly, high alkaline phosphatase & high cholesterol level favor atresia cases. Ultrasonography & liver biopsy prove to be very valuable tools in the differentiation between Biliary Atresia & Neonatal Hepatitis Syndrome.